A financial-option procedure for determining a fuzzy discount rate in radioactive waste management. (13th June 2007) - Kunsch, Pierre L.
This paper proposes a procedure based on financial-option theory for establishing a fuzzy discount rate for radioactive waste management. Funding is made available in a dedicated fund for covering future liabilities, including technical-scenario uncertainties. Assets in the fund are managed according to some given strategic asset allocation. Put-option theory is used for testing the suitability of potential discount-rate values with respect to some minimum requirements on risk levels at different time horizons. In this way, a triangular fuzzy number representing the discount rate is derived. Fuzzy funding is computed by simulation using the fuzzy discount rate: it includes an additional premium based on the put-option value to cover the residual financial risk.